Strategic Orientation of Tourism Sustainable Development: Case Study of Darband - Ebrahimi, Zahra; Mahmoudzadeh, Seyed Mojtaba (Journal of History Culture and Art Research, 2017)
Change in environment situation, attitudes, and structure are factors influential on goals of planning that finally change the program. The planning with traditional approach has not the ability to cope with these changes and would lead to failure. This condition led to the thought that planning should change direction of strategic planning and apply a new direction and behavior; this attitude underlined the innovation of strategic planning. The role of strategic direction in each strategic planning is to determine orientation and also prioritization of strategies. Since development strategy is one of the common ones, so the goal of current research is strategic detraction for development of Darband river-valley recognized by two techniques of IE and SPACE techniques. The research is of survey type performed by questionnaires among experts in the field of planning during 2013-2014. This research is an applied research performed in two levels. The first questionnaire contains internal factors (strength- weakness) and external factors (opportunity-thread) influential on Darband river-valley development. The internal factor evaluation (IFE) and external factor evaluation (EFE) tables were also completed by second questionnaire. The results showed that Darband valley is developed more than its capacity; and it not only needs to further development, but also requires management tools to improve current situation.